Analysis of School Principal Leadership Models in Improving School Performance (A Systematic Literature Review) - Madeamin Madeamin; Burhan Burhan; Muhammad Fadli; Rosnaeni Arsyad (Cerdas: Jurnal Ilmu Pendidikan Sosial dan Humaniora, 2025)
School principals play a strategic role in determining school direction and performance through effective and contextual leadership. Numerous studies indicate that principal leadership significantly influences teacher performance, instructional quality, school culture, and students’ academic achievement. However, research on educational leadership has largely focused on general approaches such as transformational and instructional leadership, while studies on local wisdom–based school leadership remain limited and have not been systematically synthesized. In fact, Indonesia’s socio-cultural diversity requires leadership models that are not only managerially effective but also culturally relevant. Therefore, this study aims to identify and analyze local wisdom–based school principal leadership models and their contributions to improving school performance. This study employed a qualitative approach using a Systematic Literature Review (SLR) method on reputable national and international journal articles published between 2015 and 2025. The literature selection process followed the PRISMA stages, including identification, screening, and systematic analysis of articles. Data were analyzed using thematic analysis to identify patterns, key themes, and research gaps. The findings reveal that local wisdom–based school leadership, through the integration of values such as mutual cooperation, deliberation, role modeling, religiosity, and social harmony, significantly contributes to strengthening school culture and climate, improving teacher performance, and enhancing school performance in a multidimensional manner. It is concluded that local wisdom–based school principal leadership represents a contextual and sustainable leadership strategy and should be developed as a key reference for strengthening educational leadership policies and practices in Indonesia.